Parametric study of radial functionally graded femoral prostheses with different geometries - Oshkour, A.A.; Talebi, H.; Shirazi, S.F.S.; Yau, Y.H.; Pramanik, S.; Tarlochan, F.; Abu Osman, Noor Azuan (2015)
Due to complex loading and chemical conditions of the human body, the artificial replacements of the body organs demand materials with superior characteristics. Therefore, recently using composite materials have gained a lot of popularity for this purpose. As a special case of the composite materials, functionally graded materials (FGMs) exhibit very interesting behavior that makes them a very suitable candidate where this study is aimed to examine the performance of femoral prostheses made of a FGM. The internal and external layers of the prostheses were composed of stainless steel and hydroxyapatite, respectively. The finite element method was used to compute the strain energy density in the proximal metaphysis of the bone, von Mises stress over the femoral prostheses, and maximum and minimum principal stress developed in the bone. The results revealed dependency of the strain energy density, interface stresses, and implanted femur component stresses on the gradient index and geometrical properties of the prostheses. Moreover, among the geometrical factors, profile and proximal cross-section were the key factors to alter strain energy density, whereas the distal cross-section effect was minor. Besides, changes in interface stresses were related to all geometrical properties of prostheses. However, stress changes in prosthesis and bone were less evident under the influence of prosthesis geometrical properties, while strains in bone showed a significant dependency to the gradient index and geometrical properties of the prosthesis.